The Social and Cultural Popularity of KKN di Desa Penari (2022): A Structural Analysis of Myths and Beliefs in Indonesian Horror Cinema (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
This study aims to analyze the factors contributing to the popularity of KKN di Desa Penari (2022) from a social and cultural perspective. Using qualitative methods, the researcher examines various narrative elements within the film that reflect social and cultural themes, drawing on Lévi-Strauss's structural theory for analysis. The findings reveal that the film’s popularity is rooted in its depiction of local myths, beliefs, and values, such as customs, human relationships with nature, and the supernatural. Additionally, the film modernizes traditional myths, making them resonate with contemporary audiences. This research contributes to the understanding of how horror films can serve as a medium for preserving and communicating cultural myths within the Indonesian context.